Quality, fruit retention and ecophysiology of 'Hass' avocado grown at two altitudes in the Andean tropics of Colombia (2023)
The expansion of 'Hass' avocado areas in the Colombian territory added to the problems associated with production, requires advancing the research efforts in order to elucidate the behavior of avocado in the conditions of the Andean tropics of Colombia. The aim of this study was to determine the effect of photosynthetically active radiation (PAR), ambient temperature, relative humidity and cardinal position of the inflorescences on the retention and final growth of 'Hass' avocado fruits in two contrasting zones of the Andean tropics of Colombia. The study was conducted in two commercial orchards located in different altitudinal zones in the department of Caldas, Colombia, Villamaría at 2,400 m above sea level (m a.s.l.) (5º01'05'' N) classified as a humid cold climate and Aranzazu at 1,900 m a.s.l. (5º18'40'' N) with semi-humid temperate climate. Evaluations were conducted on four five-year-old 'Hass' avocado trees per orchard. Monitoring was carried out on number of inflorescences that developed in each quadrant was determined and that thus learned the effect of PAR, temperature and humidity on floral development and identified the most reproductively successful quadrant of the trees in the two zones. Initial fruit set and fruit retention over time were quantified at each cardinal point of the tree. A completely randomized experimental design and Tukey's comparison of means was used. Significant differences were found PAR incidence, ambient temperature, air humidity, fruit weight and diameter according to cardinal location on the tree and locality, epidermal roughness of the fruit was higher in the lower altitude zone. The location of the different quadrants and the incidence of environmental factors it had an effect in fruit set, the final retention, size and quality of fruit at two different altitude and climatic zones of the Andean tropics of Colombia. The highest fruit retention was obtained at 1,900 m a.s.l. in the northern and western quadrants, while fruit weight and diameter were highest at 2,400 m a.s.l.